Evaluation of clinical and metabolic changes after non surgical periodontal treatment of type 2 diabetes mellitus patients: A clinico biochemical study - Kudva Praveen; Tabasum Syeda; Garg Nidhi (Wolters Kluwer Medknow Publications, 2010)
Aim: To evaluate the clinical and metabolic changes following nonsurgical periodontal therapy of type-2 diabetic patients and nondiabetic patients. Materials and Methods: Fifteen nondiabetics and fifteen type-2 diabetics with moderate to severe periodontitis were selected after meeting inclusion and exclusion criteria. Periodontal pocket probing was performed using a Williams graduated periodontal probe and comparisons of the clinical and biochemical parameters like plaque index, gingival index, probing depth, glycated hemoglobin, and lipid profile (total cholesterol, high density lipoprotein, low density lipoprotein, triglycerides and very low density lipoprotein) were done between and within two groups at baseline and 3 month. Results: A correlation was observed between clinical and biochemical parameters between and within two groups at baseline and 3 month. The P value of diabetic group was<0.001 in all clinical parameters (plaque index PI, Gingival index GI, and Probing Pocket Depth PPD) in diabetic and nondiabetic group, showed statistically highly significant difference in GI, PI, PPD, <.01 in Glycated Hemoglobulin (HbAlc1) in test group and<0.05 in control group showed statistically significant difference. The P value of test group was >0.05 in Lipid profile (total cholesterol, low density lipoprotein, high density lipoprotein, serum triglyceride, very low density lipoprotein) that showed no significant difference and in control group<0.05 in total Cholesterol, high density lipoprotein and <0.01 in Low density lipoprotein, Very Low Density Lipoprotein, and Serum Triglyceride, respectively, showed statistically significant in Total cholesterol, Low density lipoprotein, Very Low Density Lipoprotein, and Serum Triglyceride, not significant in high density lipoprotein. The P value >0.05 showed no statistical significance of correlation between the test and control groups. Conclusion: Both groups of patients showed an improvement in clinical and metabolic parameters assessed at 3 months after nonsurgical periodontal therapy.